SHEEP MEAT PRODUCTION IN AUSTRIA AND POLAND – SIMILARITIES AND DIFFERENCES - Rokicki, Tomasz; Ringdorfer, Ferdinand (Acta Scientiarum Polonorum. Oeconomia, 2020)
The aim of the article was to compare sheep meat production in Austria and Poland. The level of sheep population in both countries was similar. The sources of the materials were a literature review and data obtained from Statistics Austria and Statistics Poland. The research period concerned the years 1992–2018. Methods of data analysis were used, such as constant dynamics indicators, Gini coefficient and Lorenzo curve, Pearson correlation coefficients. A number of differences were found, e.g. in the direction of changes in the size of the sheep population, the scale of total slaughtering and industrial slaughtering, the share of self-supply in total meat production, traditional consumption of lamb during holidays, the average carcass weight of sheep, prices of lamb meat, interdependence of the sheep population with changes in economic parameters. The similarities concerned the level of concentration of the sheep population and their regional slaughtering, prejudices regarding the consumption of lamb, the share of lambs in slaughtering and meat production, the productivity of meat obtained from the slaughter of sheep.